2022
DOI: 10.3390/jcm11216341
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obstructive Sleep Apnea Syndrome on Ventricular Remodeling after Acute Myocardial Infarction: A Proof-of-Concept Study

Abstract: Background: Obstructive sleep apnea syndrome (OSA) is common in patients with acute myocardial infarction (AMI). Whether OSA impacts on the ventricular remodeling post-AMI remains unclear. We compared cardiac ventricular remodeling in patients assessed by cardiac magnetic resonance (CMR) imaging at baseline and six months after AMI based on the presence and severity of OSA. Methods: This prospective study included 47 patients with moderate to severe AMI. They all underwent CMR at inclusion and at six months af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(53 reference statements)
0
1
0
Order By: Relevance
“… 34 Recent evidence in humans indicates mild to moderate sleep apnea is common among patients with coronary artery diseases with increased LV wall thickness. 35 , 36 , 37 In addition, sleep restriction in the MI rat model leads to an enlarged heart size and concomitantly progresses to HF. 38 In line with these studies, we observed enlarged hearts with increased expression of HF markers, such as Nppa and Nppb , in Tg-SF mouse hearts compared to Tg-NSF mouse hearts.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Recent evidence in humans indicates mild to moderate sleep apnea is common among patients with coronary artery diseases with increased LV wall thickness. 35 , 36 , 37 In addition, sleep restriction in the MI rat model leads to an enlarged heart size and concomitantly progresses to HF. 38 In line with these studies, we observed enlarged hearts with increased expression of HF markers, such as Nppa and Nppb , in Tg-SF mouse hearts compared to Tg-NSF mouse hearts.…”
Section: Discussionmentioning
confidence: 99%